2018
DOI: 10.1111/evo.13632
|View full text |Cite
|
Sign up to set email alerts
|

You cannot have it all: Heritability and constraints of predator‐induced developmental plasticity in a Neotropical treefrog

Abstract: Many organisms have evolved phenotypic plasticity but examples of a heritable genetic basis or genetic constraints for plasticityacross environments remain scarce. Tadpoles of the Neotropical treefrog Dendropsophus ebraccatus alter tail coloration and shape differently in response to fish or aquatic insect predators. To assess the genetic basis of plasticity we raised 1020 tadpoles from 17 maternal half-sib pairs (34 unique families) individually with chemical cues of fish or aquatic insects, or with cue-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 112 publications
(129 reference statements)
1
22
0
Order By: Relevance
“…Among amphibians, different morphotypes within a species have been described and related to intraspecific changes in the timing of development (Collins, Zerba & Sredl, 1993), dietary conditions (Pfennig, 1990), geographical variation (Bruschi et al, 2013), or in response to predators (Kishida & Nishimura, 2005;Van Buskirk, 2017;Touchon & Robertson, 2018). The two morphs of B. riojana occurred simultaneously in the same sites and at the same developmental stages and body sizes, and with the same tooth formula, so, it is unlikely that they represent two different species or that diet or geographical variation may be directing the early appearance of the two morphotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Among amphibians, different morphotypes within a species have been described and related to intraspecific changes in the timing of development (Collins, Zerba & Sredl, 1993), dietary conditions (Pfennig, 1990), geographical variation (Bruschi et al, 2013), or in response to predators (Kishida & Nishimura, 2005;Van Buskirk, 2017;Touchon & Robertson, 2018). The two morphs of B. riojana occurred simultaneously in the same sites and at the same developmental stages and body sizes, and with the same tooth formula, so, it is unlikely that they represent two different species or that diet or geographical variation may be directing the early appearance of the two morphotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Larval amphibians are among the most studied animals for understanding predator-induced plasticity and research has examined responses in morphology [21][22][23], coloration [23][24][25], behaviour [26,27] and the timing of development [28][29][30], as well as the potential for plastic phenotypes to evolve [31]. A recent meta-analysis concluded that plastic tadpole morphological and behavioural defences positively covary but are mechanistically independent of one another [18].…”
Section: Introductionmentioning
confidence: 99%
“…There was no evidence that relatively higher tail fins caused better survival in either taxon. The large variances that rendered differences between group means (taxon, survival) non-significant ( Figs 4C and 5B) may reflect heritable variation among families in the amplitude and type of morphological plasticity [104]. This trait warrants further study using more detailed morphometrics [72].…”
Section: Plos Onementioning
confidence: 96%